Determining the sensitivity curve of Energy Dispersive X-ray Fluorescence and PIXE systems. Issue 1 (1st September 2022) - Sousa, Vitória D; Ramirez-Perez, Javier Christian; Pereira, Hugo D C; Rodrigues, Cleber L; Santos, Hellen C; Rizzutto, Márcia A
Abstract: The study of thin and thick materials every time is a challenge in X-ray analysis. The calculation of the sensitivity curve of Energy Dispersive X-ray Fluorescence (ED-XRF) and Particle Induced X-ray Emission (PIXE) systems allows for better quantitative analysis and also allows the determination of the concentration of a chemical element in a given thin sample from its intensity. The sensitivity curve can be found through the analysis of elemental standards, samples with well-defined superficial densities ( μg / cm 2 ) that allow the calculation of the sensitivity of the system to the elements present in the standards. From these standard values, it is possible to fit a curve and find the sensitivity equation as a function of the atomic number. After that, the sensitivity curve which will be used to determine the elemental composition can help to calculate the concentration of any of the chemical elements of the periodic table present in a sample. Also, PIXE and ED-XRF are known to have a different sensibility and limits of detection (LOD) to determine elemental concentrations. In this article, the sensitivities of a portable ED-XRF and a PIXE system were calculated and compared. Altogether, the results showed that, for the experimental setups used, ED-XRF has better sensitivity associated with the chemical elements of intermediate atomic numbers, while PIXE's functions describe better the sensitivities to the lighter and heavier chemical elements of the periodic table.